Soliton solutions for (2+1)-dimensional Breaking Soliton Equation: Three Wave Method - Arbabi Mohammad-Abadi, Somayeh; Najafi, malihee (International Journal of Applied Mathematical Research, 2012)
By means of the three-wave method one can solve some nonlinear partial differential equations (NLPDEs) in their bilinear forms. When an NLPDE has no bilinear closed form we can not use this method. We modify the idea of three-wave method to obtain some analytic solutions for the (2+1)-dimensional Breaking soliton equation by obtaining a bilinear closed form for it. By comparison of this method and other analytic methods, like HAM, HTA and EHTA, we can see that the new idea is very easy and straightforward.